2010
DOI: 10.1007/s10508-010-9666-4
|View full text |Cite
|
Sign up to set email alerts
|

Use and Perceptions of the Internet for Sexual Information and Partners: A Study of Young Men Who Have Sex with Men

Abstract: The Internet has opened many doors with its accessibility to information, entertainment and webbased communities. For young men who have sex with men (YMSM), the Internet can provide access to information on relevant sexual behavior and health information, stories from other men about relationship issues, and a venue for locating potential sexual and dating partners. Understanding YMSM's motivations for going online for information, advice or sexual relationships, is important as the Internet becomes increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 36 publications
3
79
1
2
Order By: Relevance
“…), to meet sex partners [6]. GSN apps provide information on geographic proximity between users making sexual partner-seeking quick and convenient [7][8][9][10]. Research among MSM who use GSN apps to find sex partners have shown mixed results regarding the relationship between GSN app use and risky sexual practices.…”
Section: Resultsmentioning
confidence: 99%
“…), to meet sex partners [6]. GSN apps provide information on geographic proximity between users making sexual partner-seeking quick and convenient [7][8][9][10]. Research among MSM who use GSN apps to find sex partners have shown mixed results regarding the relationship between GSN app use and risky sexual practices.…”
Section: Resultsmentioning
confidence: 99%
“…One study in China has reported that SOI behavior and desire sub-scale scores were associated with online sexual activity (including SEM viewing) 42 . Other studies have reported that unrestricted sociosexuality was associated with a greater odds of 21 43 and greater number lifetime sex partners 44,45 .…”
Section: Limitations Of Prior Researchmentioning
confidence: 88%
“…For example, viewing SEM may aid in the learning of performing same-sex sex 20,21 ; promote self-recognition of same-sex attractions 20,22 ; and clarify sexual self-labels 23 . However, SEM depicting male same-sex acts often contain several potentially risky sexual behaviors known to be associated with STI risk, including UAI, ejaculation in the mouth (EM), and ejaculation in/on or rubbed into the anus (EA) 24 .…”
Section: Sem Consumption and Sexual Risk Behaviors Among Msmmentioning
confidence: 99%
“…23 The Healthy Young Men's study, a longitudinal cohort study among US YMSM, found that the Internet was the most common way that study participants found their last sexual partners. 24 One YMSM study in Los Angeles found that two-thirds of respondents who used Grindr reported using the smartphone application to meet a sex partner. 25 Based on these available data, sex partners met during travel may be more likely to have met online than in person.…”
Section: Increasing Access To Sex Partners During Travel Through Onlimentioning
confidence: 99%